2023
DOI: 10.1186/s12884-023-05446-3
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal and pediatric outcomes associated with the use of fertility treatment: a population-based retrospective cohort study in Ontario, Canada

Abstract: Background Around 2% of births in Ontario, Canada involve the use of assisted reproductive technology (ART), and it is rising due to the implementation of a publicly funded ART program in 2016. To better understand the impact of fertility treatments, we assessed perinatal and pediatric health outcomes associated with ART, hormonal treatments, and artificial insemination compared with spontaneously conceived births. Methods This population-based ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…[ 9 ] report almost identical increasing prevalence of preterm birth from unassisted conception (5.9%) to subfertility without treatment (7.7%), OI/IUI treatment (8.1%) and ART (10.8%). Other studies without a subfertile untreated comparison group have reported increased risks of preterm birth and low birth weight for OI births intermediate between natural conceptions and ART births [ 12 , 13 , 30 , 31 ]. We were able to account for a greater range of chronic medical conditions and adverse obstetric history in adjusted analyses than previous studies; however, we were unable to adjust for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] report almost identical increasing prevalence of preterm birth from unassisted conception (5.9%) to subfertility without treatment (7.7%), OI/IUI treatment (8.1%) and ART (10.8%). Other studies without a subfertile untreated comparison group have reported increased risks of preterm birth and low birth weight for OI births intermediate between natural conceptions and ART births [ 12 , 13 , 30 , 31 ]. We were able to account for a greater range of chronic medical conditions and adverse obstetric history in adjusted analyses than previous studies; however, we were unable to adjust for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a miscarriage rate of 37.8%, multiple pregnancy rate of 0.7%, preterm live baby rate of 11.9% and term live baby rate of 49.7%. Dimanlig-Cruz et al in a Canadian population-based study found that crude cumulative incidences of adverse pregnancy and birth outcomes, except for small gestational age, were highest in ART pregnancies [ 26 ]. They observed, like some other European population-based studies [ 27 , 28 ], that “compared with spontaneously conceived pregnancies, ART pregnancies had significantly increased risks of stillbirth (aRR 2.26) multiple birth (aRR 8.95), cesarean delivery (aRR 1.44), preterm birth (aRR 2.06), very preterm birth (aRR 2.99), and low Apgar score (aRR 1.28)” [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dimanlig-Cruz et al in a Canadian population-based study found that crude cumulative incidences of adverse pregnancy and birth outcomes, except for small gestational age, were highest in ART pregnancies [ 26 ]. They observed, like some other European population-based studies [ 27 , 28 ], that “compared with spontaneously conceived pregnancies, ART pregnancies had significantly increased risks of stillbirth (aRR 2.26) multiple birth (aRR 8.95), cesarean delivery (aRR 1.44), preterm birth (aRR 2.06), very preterm birth (aRR 2.99), and low Apgar score (aRR 1.28)” [ 26 ]. However, a limitation of our study is that we did not compare pregnancy outcomes in ART and non-ART pregnancies during the study period, to possibly corroborate findings by Dimanlig-Cruz et al This was because many data of non-ART pregnancy outcomes during the same period were incomplete and/or missing due to their non-electronic paper documentation.…”
Section: Discussionmentioning
confidence: 99%